Variation of horizontal in situ stress with depth for long-term performance evaluation of the Deep Geological Repository project access shaft. (July 2018) - Corkum, A.G.; Damjanac, B.; Lam, T.
Abstract: A site characterization program was carried out for a proposed Deep Geological Repository (DGR) project for Ontario Power Generation's (OPG) low- and intermediate-level nuclear waste repository near Kincardine, Ontario. The repository is proposed to be constructed at approximately 680 m below ground surface within the competent argillaceous limestone of the Cobourg Formation. The in situ stress state at the project site will have significant impact on both the short- and long-term performance of repository openings, such as emplacement caverns and access shafts. As part of the site characterization program, an evaluation of the in situ stress state of the project site was conducted which consisted, primarily, of a review and synthesis of existing stress measurements conducted at various locations throughout Ontario and the midwestern U.S. Based on geomechanics data from deep boreholes and stress measurement data, a simplified FLAC3D model of the full stratigraphic profile was developed and used to simulate the influence of regional tectonic strain in the project area. In particular, this method takes into account the rock properties, such as stiffness, for discrete units at the DGR site. The model was calibrated on the basis of in situ stresses measured at Norton Mine, in a similar geological environment as the DGR site, and with site-specific borehole televiewer observations (i.e., breakouts). The model-predicted horizontal in situ stress profile showed general agreement with the observations and also showed the significant influence of discrete rock unit stiffness. Graphical abstract: fx1 Highlights: A literature review of compiled in situ stress data for Ontario, Canada is presented. Variation in geological formation stiffness impacts horizontal stresses. A simplified FLAC3D model was developed to account for the stratigraphic profile. Model calibrated by borehole breakouts, stress measurements and observations. An improved estimate of the horizontal stress profile was developed.